2005
DOI: 10.1111/j.1365-2559.2005.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

CD117+ small cell lung cancer lacks the asp 816→val point mutation in exon 17

Abstract: The absence of mutations in exon 17 of CD117+ SCLC suggests this tumour may respond to therapy with TKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The protein expression in SCLC varies among researchers [6][7][8][9][10][11][12][13][14][15]; the percentage ranges from 30 [15] to 80% [6]. It is reported that KIT expression without KIT gene mutations is due to KIT gene amplification [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The protein expression in SCLC varies among researchers [6][7][8][9][10][11][12][13][14][15]; the percentage ranges from 30 [15] to 80% [6]. It is reported that KIT expression without KIT gene mutations is due to KIT gene amplification [15].…”
Section: Discussionmentioning
confidence: 99%
“…KIT and PDGFRA mutations are frequent in GIST [19]. With regard to SCLC, almost all reports showed no KIT mutations [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of SCLC revealed that KIT protein is expressed in a significant percentage of SCLC [9][10][11][12][13][14][15][16][17][18]. In addition, one report showed that KIT gene mutations were present in SCLC [16], but others did not [15,17,18].…”
Section: Introductionmentioning
confidence: 99%